Diversity and pitfalls of pancreatic neuroendocrine tumors: A case series of cytologic-histologic correlation - Christopher C. Attaway; Zhaohai Yang; Roseann I. Wu (Elsevier, 2022)
Pancreatic neuroendocrine tumors (PanNETs) represent a morphologically heterogeneous group which can prove challenging for pathologists to diagnose by cytology. The index case was initially misdiagnosed on an endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) as metastatic pancreatic adenocarcinoma with signet ring cell morphology; however, the resected surgical pathology specimen was histologically and immunohistochemically compatible with a well-differentiated neuroendocrine tumor with rhabdoid features. In light of the resection specimen, the cytopathology specimen was reviewed, with the spectrum of morphology appreciated in retrospect. This case prompted a search within our institution for challenging cases that highlight the gamut of PanNET morphologies. In this series, the cases presented highlight benign mimickers, rare diagnoses, differential diagnostic considerations, and the overlapping morphologies that PanNETs can exhibit in cytology specimens with comparison to their surgical counterparts. Specific importance is placed on morphology and immunohistochemistry to distinguish between PanNET and the differential diagnoses of ductal adenocarcinoma, clear cell variant of PanNET, neuroendocrine carcinoma, solid pseudopapillary neoplasm, and acinar cell carcinoma, as well as islet cell hyperplasia and nesidioblastosis, with important attention to interpretation of paucicellular specimen. Furthermore, we provide a review of immunohistochemical studies in cases where morphology is especially challenging.